2017
DOI: 10.1186/s12891-017-1896-3
|View full text |Cite
|
Sign up to set email alerts
|

Multisite peripheral joint pain: a cross-sectional study of prevalence and impact on general health, quality of life, pain intensity and consultation behaviour

Abstract: BackgroundResearch into musculoskeletal conditions often focusses on pain at single sites, such as the knee, yet several studies have previously reported the high prevalence of multiple sites of musculoskeletal pain. The most common form of musculoskeletal condition is arthritis, with osteoarthritis (OA) the most common cause of joint pain in adults 45 years and over. However, there is limited recognition of the prevalence of multisite peripheral joint pain in those either living with or at risk of OA, therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 25 publications
7
28
0
2
Order By: Relevance
“…In the research by Kazemi et al (2016), WMSDs had a profound effect on general health, and general health had a significantly, negative correlation with occupational stress. Similarly, Finney et al (2017) reported a significant association between multisite peripheral joint pain and poor general health [25][26][27][28]. The aforementioned findings are consistent with the results of the present study.…”
Section: Resultssupporting
confidence: 92%
“…In the research by Kazemi et al (2016), WMSDs had a profound effect on general health, and general health had a significantly, negative correlation with occupational stress. Similarly, Finney et al (2017) reported a significant association between multisite peripheral joint pain and poor general health [25][26][27][28]. The aforementioned findings are consistent with the results of the present study.…”
Section: Resultssupporting
confidence: 92%
“…Back pain and hip pain were independently associated with moderate-to-severe foot pain and this finding is in agreement with a large body of evidence demonstrating strong associations between foot pain and other regional bodily pain [ 3 , 4 , 37 ]. Multi-site joint problems have been identified as common and are associated with increasing age, the presence of comorbidities and social deprivation [ 37 , 79 ]. Recent evidence suggests that multi-site joint pain prevalence is increasing and that more holistic management strategies are required whereby health professionals consider joint pain beyond the primary site [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis and subsequent treatment are often focused on a single, most painful joint rather than multisite joint problems [ 11 ]. Yet multisite joint pain is the most common presentation in consultations in primary care, and having more joint sites affected leads to more health care consultations irrespective of specialty or site [ 11 ].…”
Section: Challenges and Gaps In Carementioning
confidence: 99%
“…Diagnosis and subsequent treatment are often focused on a single, most painful joint rather than multisite joint problems [ 11 ]. Yet multisite joint pain is the most common presentation in consultations in primary care, and having more joint sites affected leads to more health care consultations irrespective of specialty or site [ 11 ]. As summarized in a recent systematic review, there is a paucity of evidence to guide the practitioner regarding treatment of multisite joint pain, with few studies describing interventions for considering OA in all affected joints [ 12 ].…”
Section: Challenges and Gaps In Carementioning
confidence: 99%